Measuring Level of Students' Independent Learning In Distance Learning - Annisa Nuraeni Rahayu; Siti Mujdalipah; Dwi Lestari R (LPPM Universitas Terbuka, 2022)
This study aims to determine the level of students' independent learning based on indicators of independent learning in terms of the process and management of students when they were studying. When students learn independently, it plays an important role in learning success and helping students obtained optimal learning outcomes. This research was used analytic descriptive research methods and survey techniques, used four indicators of independent learning in terms of the process and management of students when they were studying. The results showed that most of the students had independent learning in high to very high categories on the indicators of having initiative and motivation to learning, able to diagnose learning needs, able to determine learning targets and learning goals, and able to monitor, organize, and control learning. The results showed that almost all students had a level of independent learning in the high to the very high category on those three indicators.